New voltage sag detection based on phase angle analysis for the new topology of voltage sag compensator - Rahim, N.A.; Mansor, M. (IEICE-Inst Electronics Information Communications Eng, 2010)
This paper implements two main works. First, a new voltage-sag detection technique based on phase-angle analysis is proposed. It is simple to implement and able to detect and compensate sag the moment it occurs. Second, a new topology of voltage sag compensator is introduced. The proposed topology is able to reduce stress effect due to current flows into the switches and avoid non-stop operation during sag events. This proposed work had been verified and investigated by developing a laboratory prototype where a TMS320F2812 DSP is used as the main controller.